2001
DOI: 10.1017/s0012162201000056
|View full text |Cite
|
Sign up to set email alerts
|

Contact and nutrient caregiving effects on newborn infant pain responses

Abstract: To understand how the 'caregiving context' could affect responses to procedural pain, the authors sought to determine whether (1) the combined effects of sweet taste and holding (caregiving contact) were greater than the effects of either alone, (2) any combined effects were additive or interactive, and (3) the interventions had similar effects on behavioral (crying and facial activity) and physiological (heart rate, vagal tone) responses to the heel-stick procedure in newborn infants in a randomized two-facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1
12

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 64 publications
2
37
1
12
Order By: Relevance
“…49 Recently it has been suggested that more attention needs to be paid to environmental adaptations to manage pain, complementary to use of pharmacologic agents. 50 Positioning and containment, 51 music, 52 sucking, 53 suckling, 54 and kangaroo care, 55 for example, may facilitate early "coping" with stressful intervention. Effective environmental interventions enhance homeostasis and stability in preterm infants in the NICU and are essential elements of neonatal nursing care.…”
Section: Discussionmentioning
confidence: 99%
“…49 Recently it has been suggested that more attention needs to be paid to environmental adaptations to manage pain, complementary to use of pharmacologic agents. 50 Positioning and containment, 51 music, 52 sucking, 53 suckling, 54 and kangaroo care, 55 for example, may facilitate early "coping" with stressful intervention. Effective environmental interventions enhance homeostasis and stability in preterm infants in the NICU and are essential elements of neonatal nursing care.…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen of the 29 articles selected were studies of fullterm neonate patient samples, [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] eleven studied preterm neonates [33][34][35][36][37][38][39][40][41][42][43] and two included comparisons between preterm and fullterm neonates. 44,45 The volume of sucrose used in the majority of the studies involving fullterm neonates was 2 ml, [17][18][19][20][21][22][23][24][25][27][28][29][30][31][32] with concentrations of 12%, 20,24,30,31 12.5%, 18,32 24%, …”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies 18,19,21,24,26,30,32,35,36,41,42 assessed facial actions (brow bulge, eye squeeze, nasolabial furrow, open lips, mouth stretch (horizontal and vertical), lip purse, tongue tautening, and chin quiver,) using the Neonatal Facial Coding System (NFCS), which is a one-dimensional instrument validated for evaluation of the response to neonatal pain. Two studies 19,39 evaluated body movements (upper and lower limbs) using a validated one-dimensional instrument, the Infant Body Coding System (IBCS).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations